Debilitating Lung Disease Among Surface Coal Miners With No Underground Mining Tenure. Issue 1 (January 2015) - Halldin, Cara N.; Reed, William R.; Joy, Gerald J.; Colinet, Jay F.; Rider, James P.; Petsonk, Edward L.; Abraham, Jerrold L.; Wolfe, Anita L.; Storey, Eileen; Laney, A. Scott
<x xml:space="preserve">Abstract</x> Objective: To characterize exposure histories and respiratory disease among surface coal miners identified with progressive massive fibrosis from a 2010 to 2011 pneumoconiosis survey. Methods: Job history, tenure, and radiograph interpretations were verified. Previous radiographs were reviewed when available. Telephone follow-up sought additional work and medical history information. Results: Among eight miners who worked as drill operators or blasters for most of their tenure (median, 35.5 years), two reported poor dust control practices, working in visible dust clouds as recently as 2012. Chest radiographs progressed to progressive massive fibrosis in as few as 11 years. One miner's lung biopsy demonstrated fibrosis and interstitial accumulation of macrophages containing abundant silica, aluminum silicate, and titanium dust particles. Conclusions: Overexposure to respirable silica resulted in progressive massive fibrosis among current surface coal miners with no underground mining tenure. Inadequate dust control during drilling/blasting is likely an important etiologic factor.